Gliclazide MR in the structure of antihyperglycemic therapy according to the data of Moscow region diabetes register - I. V. Misnikova; Yu. A. Kovaleva; V. A. Gubkina; A. V. Dreval (Сахарный диабет)
Background: Sulfonylureas (SU) are often used for second and third line type 2 diabetes mellitus (T2DM) therapy. Currently, there are no unified recommendations governing the choice of drugs for the second line therapy. This requires clarification.Aim: To examine Moscow Region DM register data for assessing ongoing antihyperglycemic therapy and its correspondence to current local and international T2DM treatment recommendations, as well as actual clinical recommendations for the treatment of T2DM patients and COVID-19.Materials and methods: The structure of glucose-lowering therapy with non-insulin drugs (NID) was studied in T2DM patients according to the data T2DM register of Moscow region. The analysis was carried out on 06.02.2021. We analyzed the general group of T2DM patients (237479 people), group 60 years and older (188644 patients), T2DM patients who have had COVID-19. Newly diagnosed T2DM individuals were analyzed for 2020 (5088 people).Results: Glucose-lowering therapy is received by 97.6% of T2DM patients. Of these, 79.07% take NID, insulin + NID - 11.37%. Monotherapy is received by 44.4% of patients, a combination of two drugs - 29.3%, out of three - 5.3% of patients. Metformin is the leader in prescribing NID (69.4% of all T2DM patients and 81.3% in newly diagnosed patients). SU are in second place in T2DM treatment (50% of all patients, 24.1% in newly diagnosed patients), iIDPP-4 is in third place (12.1% and 12.6%, respectively). Among patients of 60 and more years old, 25.99% of patients take gliclazide MR, 14.3% glibenclamide, 7.7% glimepiride. Mortality from COVID-19 depends on the diabetes duration.Conclusion: According to the DM register, half of the T2DM patients and a quarter of T2DM newly diagnosed patients get SU. As a first-line drug, SU is on the second place after metformin and are most often used in double and triple combinations of T2DM therapy. In the older age group on SU, preference is given to gliclazide MR.